An assessment of vertigo patients presenting to the otorhinolaryngology and neurology outpatient clinics - Sarıca, Selman; İnanç, Yılmaz; İnanç, Yusuf (The European Research Journal, 2019)
Objective: Vertigo is a general term used for disorientation and is a frequent cause of admission to emergency services, otorhinolaryngology and neurology outpatient clinics. This study aims to evaluate the clinical findings, diagnostic laboratory tests, brain magnetic resonance imaging, and Doppler ultrasonography results of patients with complaints of vertigo.Methods: Patients aged >18 years who admitted to the Otorhinolaryngology and Neurology Outpatient clinics of Kahramanmaraş Sütçü İmam University Training and Research Hospital with the main complaint of vertigo between January 2017 and August 2017 were retrospectively reviewed. The patients were evaluated in respect of anamnesis, examination findings, and diagnostic tests (pure tone audiometry, video nystagmography, brain magnetic resonance imaging, and carotid and vertebral artery Doppler ultrasonography).Results: The study included a total of 101 patients with a mean age of 46.36 ± 16.1 years who presented with the complaint of vertigo. Of the patients, 16 had an ischemic gliotic region, 4 had a lacunar infarct, 2 had an arachnoid cyst, 2 had a cerebellar infarct, 1 had a meningioma, and 1 had a pineal gland cyst on the brain magnetic resonance imaging. Of the patients evaluated in the Otorhinolaryngology outpatient clinic, 87 (86.13%) were diagnosed with peripheral vertigo and 14 (13.6%) with central vertigo. A diagnosis of central vertigo was made in 23 (22.77%) patients evaluated in the Neurology outpatient clinic. Conclusions: For patients presenting with the complaint of vertigo to the otorhinolaryngology and neurology outpatient clinics, a detailed anamnesis and a physical examination precede specific vestibular tests in the diagnosis. A coordinated communication of both clinics is important for a rapid diagnosis and prevention of unnecessary examinations.